Emergent Curriculum in the Form of Creative Class in Kindergarten - Antara, Putu Aditya (Universitas Pendidikan Ganesha, 2021)
The implementation of an emergent curriculum that is developed spontaneously based on children's interests needs to be balanced by a creative class so that learning in class will be very fun for children. This study aims to analyze the potential for implementing an emergent curriculum based on creative classes in kindergarten. This type of research is a qualitative case study approach with data sources derived from observations, interviews, and documentation. The unit of analysis in this study were teachers, principals, and children with a total of 210 people. The data analysis used adopted the Miles and Huberman analysis model which was carried out in four steps, namely data collection, data reduction, data presentation, and verification or concluding. The results showed that the emergent curriculum based on creative classes in terms of indoor classes was found not to be dynamic, conducive, and ideal to be able to increase children's creativity, but the institution had used the area learning model but it was not optimal in its realization. While the outdoor class has been done neatly and beautifully, but the children have not been well organized when playing in the schoolyard, even though the development of children outdoors is good stimulation for children so that they can be stimulated in various conditions while in kindergarten institutions. -child. In addition, the classroom atmosphere has not been developed creatively and imaginatively even though many parts of the class can be maximized, such as walls being used to periodically display children's works. For this reason, principals and teachers need to be given self-development in the field of the creative classroom-based emergent curriculum so that principals and teachers can carry out the learning process in a spontaneous atmosphere but still on target and according to the interests of the child's potential.